Zolpidem Profoundly Augments Spared Tonic GABAAR Signaling in Dentate Granule Cells Ipsilateral to Controlled Cortical Impact Brain Injury in Mice - Boychuk, Jeffery A.; Butler, Corwin R.; Smith, Katalin Cs.; Halmos, Miklos B.; Smith, Bret N. (Frontiers in Systems Neuroscience, 2022)
Type A GABA receptors (GABAARs) are pentameric combinations of protein subunits that give rise to tonic (ITonicGABA) and phasic (i.e., synaptic; ISynapticGABA) forms of inhibitory GABAAR signaling in the central nervous system. Remodeling and regulation of GABAAR protein subunits are implicated in a wide variety of healthy and injury-dependent states, including epilepsy. The present study undertook a detailed analysis of GABAAR signaling using whole-cell patch clamp recordings from mouse dentate granule cells (DGCs) in coronal slices containing dorsal hippocampus at 1–2 or 8–13 weeks after a focal, controlled cortical impact (CCI) or sham brain injury. Zolpidem, a benzodiazepine-like positive modulator of GABAARs, was used to test for changes in GABAAR signaling of DGCs due to its selectivity for α1 subunit-containing GABAARs. Electric charge transfer and statistical percent change were analyzed in order to directly compare tonic and phasic GABAAR signaling and to account for zolpidem’s ability to modify multiple parameters of GABAAR kinetics. We observed that baseline ITonicGABA is preserved at both time-points tested in DGCs ipsilateral to injury (Ipsi-DGCs) compared to DGCs contralateral to injury (Contra-DGCs) or after sham injury (Sham-DGCs). Interestingly, application of zolpidem resulted in modulation of ITonicGABA across groups, with Ipsi-DGCs exhibiting the greatest responsiveness to zolpidem. We also report that the combination of CCI and acute application of zolpidem profoundly augments the proportion of GABAAR charge transfer mediated by tonic vs. synaptic currents at both time-points tested, whereas gene expression of GABAAR α1, α2, α3, and γ2 subunits is unchanged at 8–13 weeks post-injury. Overall, this work highlights the shift toward elevated influence of tonic inhibition in Ipsi-DGCs, the impact of zolpidem on all components of inhibitory control of DGCs, and the sustained nature of these changes in inhibitory tone after CCI injury.